Propuesta de mejora a los procesos de Coordinación de Año de las Carreras de la ESPAM MFL - García Lucas, Rommel Michael (2017)
The analysis of the year coordination processes was designed to improve the effectiveness of the activities, in the first instance a field study was carried out, which consisted, in an observation and direct interview To the involved ones, allowing to represent the procedures developed: evaluation and correction of the documents of educational programming, socialization of regulations and reports; Consecutively, we performed the AVA (value added analysis) to each of the subprocesses, in conjunction with the times, personnel involved, helping to discern activities that add value and do not generate: sending documents, receiving , Finding, being necessary the consensus with the implicated ones to determine if its function is fundamental for the attainment of the objectives. Lastly, proposals for improvements in the processes developed by the year coordinators were designed, allowing the determination of the importance of visualizing and representing the processes through a functional diagram, which, through the analysis of added value, Pace with which year coordinators perform can still be optimized.